Effect of plant and animal based compost on the growth and yield of Okra (Abelmoschus esculentus) in a Nigeria-derived Savanna - Michael Ati Kekong; Nmadzuru Badeggi Ibrahim (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: The limitation of the use of some agricultural wastes is their C/N ratio. This study was aimed at integrating cocoa pod husk, moringa leaves, and poultry droppings in composted form for enriched soil amendments for vegetable production. Method: Three compost types: cocoa pod husk, moringa leaf, and poultry droppings were composted for 60 days in a ratio of 3:1:1, 3:1, and 3:1, respectively. Each compost type was applied at the rate of 2.5, 5.0, 7.5, and 10 t ha-1 with a zero control and an optimal control of NPK 20.10.10 at 200kgha-1. The treatments were 14 which were laid out in RCBD and replicated thrice. The effect of the compost manures was assessed on the growth, yield, and yield components of Okra in two seasons. Results: The results indicated that Compost1, Compost 2, and Compost 3 at a rate of 10 t ha-1 produced significantly (P<0.05) the tallest plants with the least height in the zero control. The leaf area result indicated that Compost1, Compost 2, and Compost 3 at 10 t ha-1 and NPK 20.10.10 produced the largest leaves and highest number of fruits per plant. Fruit yield was highest (P<0.05) in Compost1 at 10 t ha-1 in 2020 and 2021 (8.6t ha-1 and 8.8t ha-1), respectively and the least in the zero control. Conclusion: The result from this study showed that the integration of cocoa pod husk, Moringa leaf, and poultry droppings in composted form is a suitable organic amendment for optimal production of okra in Nigeria-derived savanna.